Therapeutic Effect of Camel Milk and Its Exosomes on MCF7 Cells In Vitro and In Vivo. (December 2018) - Badawy, Abdelnaser A.; El-Magd, Mohammed A.; AlSadrah, Sana A.
Background/Objectives: In the Middle East, people consume camel milk regularly as it is believed to improve immunity against diseases and decrease the risk for cancer. Recently, it was noted that most of the beneficial effects of milk come from their nanoparticles, especially exosomes. Herein, we evaluated the anticancer potential of camel milk and its exosomes on MCF7 breast cancer cells (in vitro and in vivo) and investigated the possible underlying molecular mechanism of action.Methods/Results: Administration of camel milk (orally) and its exosomes (orally and by local injection) decreased breast tumor progression as evident by ( a ) higher apoptosis (indicated by higher DNA fragmentation, caspase-3 activity, Bax gene expression, and lower Bcl2 gene expression), ( b ) remarkable inhibition of oxidative stress (decrease in MDA levels and iNOS gene expression); ( c ) induction of antioxidant status (increased activities of SOD, CAT, and GPX), ( d ) notable reduction in expression of inflammation-( IL1b, NFκB ), angiogenesis-( VEGF ) and metastasis-( MMP9, ICAM1 ) related genes; and ( e ) higher immune response (high number of CD + 4, CD + 8, NK1.1 T cells in spleen).Conclusions: Overall, administration of camel milk–derived exosomes showed better anticancer effect, but less immune response, than treatment by camel milk. Moreover, local injection of exosomes led to better improvement than oral administration. These findings suggest that camel milk and its exosomes have anticancer effect possibly through induction of apoptosis and inhibition of oxidative stress, inflammation, angiogenesis and metastasis in the tumor microenvironment. Thus, camel milk and its exosomes could be used as an anticancer agent for cancer treatment.